Produção e gestão de podcast: um guia de adoção para as organizações - SOUSA, Jefferson Saylon Lima de (2022)
The present work consists of applied research focusing on the development of a hypermedia tool to be used by communication professionals directly linked to the environment of organizations. It is a guide for the adoption of the podcast as part of the media actions of these institutions considering its characteristics as a hypermedia product and also the particularities of organizational communication. In order to do so, it uses the discussion about the concept of hypermedia, its differentiation as a language and communication process, aiming to establish a connection between the properties and principles of hypermedia and the applicability of the podcast in cyberspace. From the definition of what a podcast is and how it is structured, its presence in the communicational environment of organizations is discussed, listing its role as a tool for spreadability messages and image of these institutions, tracing an expository profile of the podcast's performance scenarios within communication. integrated organizational structure detailing its focus on institutional and marketing compounds through journalism and marketing practices. In this way, the organizational podcast is listed as a genre present in this media and that - from its peculiarities and dialogues in the organization - can be produced in three respective formats: roundtable, storytelling and drop. From this knowledge, it is proposed the elaboration of the hypermedia guide from the adequacy of the knowledge acquired through research and observation of existing models being executed in two formats: an e-book in PDF and a website. Both formats are connected in order to provide an expanded content of discussions regarding podcast media and its execution in an organization. In order to conceive the artifacts, it is based on the Design Science stages as a project coordination metric, applying the hypermedia design methodology in the construction of interfaces and hyperlink structures to be executed during the formatting of the guide.